2020
DOI: 10.1007/s00259-020-04797-9
|View full text |Cite
|
Sign up to set email alerts
|

Prior therapies as prognostic factors of overall survival in metastatic castration-resistant prostate cancer patients treated with [177Lu]Lu-PSMA-617. A WARMTH multicenter study (the 617 trial)

Abstract: Introduction The impact of prior therapies, especially chemotherapy, on overall survival (OS) in patients with castration-resistant prostate cancer (CRPC) receiving [ 177 Lu]Lu-PSMA-617 therapy has been the subject of controversy. Therefore, WARMTH decided to plan a multicenter retrospective analysis (the “617 trial”) to evaluate response rate and OS as well as the impact of prior therapies on OS in more than 300 patients treated with 177 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
115
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(133 citation statements)
references
References 27 publications
15
115
2
1
Order By: Relevance
“…This is in line with previous findings demonstrating that the presence of visceral metastases, especially liver metastases, results in poorer survival [20] [21]. ECOG status has also been identified as a prognosticator of OS before [22]. The extent of metastases on PSMA ligand PET/CT was only a significant prognostic marker on univariate analysis.…”
Section: Discussionsupporting
confidence: 91%
“…This is in line with previous findings demonstrating that the presence of visceral metastases, especially liver metastases, results in poorer survival [20] [21]. ECOG status has also been identified as a prognosticator of OS before [22]. The extent of metastases on PSMA ligand PET/CT was only a significant prognostic marker on univariate analysis.…”
Section: Discussionsupporting
confidence: 91%
“…Although the prognosis is generally favorable [2], the treatment of PC is challenging in the cases of metastatic castration-resistant prostate cancer (mCRPC) [3]. The prostate-specific membrane antigen (PSMA) is a transmembrane protein and highly expressed in PC cells [1,4]. Radioligands targeting PSMA are promising agents for the imaging and treatment of PC patients [1,[5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…The aim of our study was analysis of early changes in quality of life in prostate cancer patients after the first cycle of 177 Lu-PSMA-617 therapy and its association with alterations in PSA. Recent analyses have proven the efficacy of PSMA treatment compared to standard treatment for metastatic castration-resistant prostate cancer (mCRPC) [3,[11][12][13][14][15]. The most recent systematic review and meta-analysis [11] covering all studies published up to August 2018 on the efficacy and safety of 177 Lu-PSMA-617 RLT included 17 original articles on altogether 744 patients.…”
Section: Discussionmentioning
confidence: 99%
“…The latest published papers about radioligand therapy (RLT) with 177 Lu-PSMA-617 showed that the treatment is well tolerated and has a low toxicity profile [1,2]. First results have indicated that this therapy further has a positive impact on the prolongation of overall survival (OS) [1,3]. Apart from a prolongation of OS and low toxicity profile the best clinical outcome for the patients would be achieved when a new therapy has also a positive influence on quality of life (QoL).…”
Section: Introductionmentioning
confidence: 99%